Urgensi Komunikasi dalam Kelompok Kecil untuk Mempercepat Proses Adopsi Teknologi Pertanian - Cut Rabiatul Adawiyah (Forum penelitian Agro Ekonomi, 2017)
Adoption process of effective agricultural technology innovation requires various forms and channels of communication between users. Personal communication between individuals and communication in small groups (farmers’ group) are two forms of communication that has been used as a mainstay in agricultural extension activities. Personal communication usually occurs horizontally between farmers, and vertically between farmers and agricultural extension officers. Personal communication between farmers can take place outside and also within farmers’ groups. This paper is a review of various theories and research results regarding the importance of communication in small groups. The results showed that communication in small groups becomes an important component in delivering information materials, i.e. technology and other information. In the group, in addition to ongoing communication, it is also a place of performing discussion and learning among peasants, as well as a unit of decision for unity of action in adopting technology. AbstrakProses adopsi inovasi teknologi pertanian yang efektif membutuhkan beragam bentuk dan saluran komunikasi antar pelakunya. Komunikasi personal antar individu serta komunikasi dalam kelompok kecil (kelompok tani) merupakan dua bentuk komunikasi yang selama ini dijadikan sebagai andalan dalam kegiatan penyuluhan pertanian. Komunikasi personal biasanya terjadi secara horizontal antar petani, dan secara vertikal antar petani dengan petugas penyuluh pertanian. Komunikasi personal antar petani dapat berlangsung di luar dan juga di dalam kelompok tani. Tulisan ini merupakan review ilmiah dari berbagai teori dan hasil-hasil penelitian berkenaan dengan pentingnya peran komunikasi dalam kelompok kecil. Hasil telaahan menunjukkan bahwa komunikasi dalam kelompok kecil menjadi komponen penting dalam menyampaikan materi informasi baik berupa teknologi maupun informasi lain. Di dalam kelompok, selain berlangsung komunikasi juga sekaligus menjadi tempat diskusi dan belajar antar sesama petani, di samping sebagai unit keputusan untuk kesatuan tindakan dalam mengadopsi teknologi.